2015
DOI: 10.1139/cjfas-2014-0238
|View full text |Cite
|
Sign up to set email alerts
|

Range-wide age and growth characteristics of shovelnose sturgeon from mark–recapture data: implications for conservation and management

Abstract: We used mark-recapture data from shovelnose sturgeon (Scaphirhynchus platorynchus) to describe range-wide growth characteristics and developed a model to estimate ages. Data were solicited throughout much of the current distribution of shovelnose sturgeon, specifically from the mainstem Missouri and Mississippi rivers and their tributaries. Shovelnose sturgeon exhibited variable growth among locations; however, adult fish exhibited almost no growth after they reached a particular size, presumably the size at s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 39 publications
1
34
0
Order By: Relevance
“…We observed negligible growth in shovelnose sturgeon and very slow growth in blue sucker, <1% per year. A meta‐analysis of 14 shovelnose sturgeon populations (including the LWR) throughout the species range concluded that most fish had almost no growth in length after they reached maturity (Hamel et al., ). In the Red Cedar‐Chippewa River system, Wisconsin, recaptured shovelnose sturgeon had only grown an average of 0.75 mm/year since tagging (Christenson & Hatzenbeler, ), well within the range of measurement error (Phelps et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed negligible growth in shovelnose sturgeon and very slow growth in blue sucker, <1% per year. A meta‐analysis of 14 shovelnose sturgeon populations (including the LWR) throughout the species range concluded that most fish had almost no growth in length after they reached maturity (Hamel et al., ). In the Red Cedar‐Chippewa River system, Wisconsin, recaptured shovelnose sturgeon had only grown an average of 0.75 mm/year since tagging (Christenson & Hatzenbeler, ), well within the range of measurement error (Phelps et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…These three aforementioned explanations are not mutually exclusive and could all be occurring in the LWR, although we believe that number three is most important. A von Bertalanffy analysis for LWR shovelnose sturgeon estimated a maximum age of over 60, the highest of any of 14 populations analyzed (Hamel et al., ). However, the oldest ages ever actually reported for any populations based on fin rays were 43 for shovelnose sturgeon (Everett et al., ) and 37 for blue sucker (Bednarski & Scarnecchia, ).…”
Section: Discussionmentioning
confidence: 99%
“…Such mark-recapture studies can provide a nonlethal way to monitor and assess population characteristics, thus being an effective tool for monitoring endangered species. Specifically, the information that can be provided by mark-recapture studies includes insight into growth, recruitment, and mortality, providing insight into the ecological function of a species which is essential for fisheries conservation and restoration decisions (Gibbons and Andrews, 2004;Ruetz III et al, 2006;Skalski et al, 2009;Hamel et al, 2015;Ruetz III et al, 2015). Mark-recapture studies are an effective tool when evaluating population dynamics and ecological role and can allow researchers the ability to make better restoration decisions concerning grotto sculpin and the cave ecosystems they inhabit.…”
Section: Discussionmentioning
confidence: 99%
“…Previous researchers have used mark-recapture studies to evaluate fish population dynamics (Hamel et al, 2015;Ruetz III et al, 2015). Data garnered from these studies generally include measures of growth, movement, habitat use, and survival, all of which are imperative for fisheries conservation or restoration (Hamel et al, 2015;Ruetz III et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation